Tree-structured multi-layer fuzzy cognitive maps for modelling large scale, complex problems - Andreou, Andreas S.; Mateou, Nicos (My University, 2005)
This paper proposes tree structured Multi-Layer Fuzzy Cognitive Maps for modelling large-scale and complex real world problems and supporting the decision making process. Large-scale problems are characterized by a large number of parameters, concepts, variables, nonlinearities and uncertainties that make their analysis and modelling a very difficult task. The objective of the proposed methodology is to give an alternative approach for dealing with the aforementioned difficulties, offering a new computational algorithm designed so as to support the creation of layers of parameters and variables describing the system under study, as well as the simulation of its evolution dynamics. © 2005 IEEE.
Keywords: Structured programming; Cognitive systems; Large scale systems; Mathematical models; Problem solving; Self organizing maps; Trees (mathematics)